Proliferative capacity of epitope-specific CD8 T-cell responses is inversely related to viral load in chronic human immunodeficiency virus type 1 infection. - Day, C; Kiepiela, P; Leslie, A; van der Stok, M; Nair, K; Ismail, N; Honeyborne, I; Crawford, H; Coovadia, H; Goulder, P; Walker, B; Klenerman, P (2007)
The relationship between the function of human immunodeficiency virus (HIV)-specific CD8 T-cell responses and viral load has not been defined. In this study, we used a panel of major histocompatibility complex class I tetramers to examine responses to frequently targeted CD8 T-cell epitopes in a large cohort of antiretroviral-therapy-naïve HIV type 1 clade C virus-infected persons in KwaZulu Natal, South Africa. In terms of effector functions of proliferation, cytokine production, and degranulation, only proliferation showed a significant correlation with viral load. This robust inverse relationship provides an important functional correlate of viral control relevant to both vaccine design and evaluation.